Difficulties in Speaking Skill Encountered by English Students at Tadulako University - Puspasari, Devi; Jamiluddin, Jamiluddin; Kamaruddin, Abdul (ITScience (Information Technology and Science), 2025)
This study aims to identify the difficulties in speaking English and the factors influencing these difficulties among the students. The research design used is a qualitative method with the subjects of the research being the fourth-semester students in the English Education Study Program at Tadulako University. The researcher used questionnaires and interviews as data collection tolos. Based on the data análisis results, there are three predominant speaking difficulties faced by most students. First, the diffculty in expressing ideas clearly and effectively. Second, the difficulty in using correct grammar. Third, the difficulty in dealing with anxiety while speaking. The factors influencing these difficulties are divided into two main categories: linguistic factors and psychological factors. Linguistic factors relate to language elements such as limited vocabulary, improper grammar usage, and nuclear pronunciation. Psychological factors include individual psychological aspects such as low self-confidence, lack of motivation, and high levels of anxiety. The findings of this study are expected to provide insights for educators to develop strategies to help students overcome these challenges and improve their speaking skills.